A longitudinal investigation of a multidimensional model of social support and physical activity over the first year of university. (July 2017) - Scarapicchia, Tanya M.F.; Sabiston, Catherine M.; Pila, Eva; Arbour-Nicitopoulos, Kelly P.; Faulkner, Guy
Abstract: Objectives: University students report numerous barriers to physical activity participation including a lack of social support. Yet little is known about the types and providers of social support that are associated with physical activity across the first year of university. Design: Prospective longitudinal survey. Method: Undergraduate students ( N  = 819; 64% female) completed a self-report survey at the beginning of their first year in university, near the end of first year, and at the beginning of second year. Data were analyzed using multilevel modeling to examine the associations between social support and physical activity over time. Results: Based on unconditional growth models, physical activity increased (β = 14.82), whereas received family support (β = −0.10), and number of people providing tangible support (β = −0.04) decreased over the first year of university. Students reported engaging in higher amounts of physical activity during times when they had more, compared to less than their average, social network from family (β = 23.20) and received social support from friends (β = 34.87). These results were similar at the between-person level. Living status emerged as a moderator of the association between tangible support satisfaction and physical activity, revealing a positive association (β = 29.72) for individuals living on/around campus. Conclusions: The relationship between social support and physical activity varies at both within-person and between-person levels. Family providers of support appear to continue to influence the physical activity levels of university students. As such, university physical activity programs could endorse multiple dimensions and providers of social support. Highlights: Number of active family members predicts physical activity across first year of university. Received support from friends is important for physical activity among university students. Students who are satisfied with tangible support for physical activity are more active. University physical activity programming could be enhanced with a focus on social support from family and friends.